Lactobacillus plantarum surface-displayed FomA (Fusobacterium nucleatum) protein generally stimulates protective immune responses in mice - Zhang, Xiaoyu; Xiao, Huijie; Zhang, Huaiyu; Jiang, Yang (Frontiers in Microbiology, 2023)
： A significant correlation is observed between Fusobacterium nucleatum (F. nucleatum) and the evolution of inflammatory bowel disease (IBD). Particularly, FomA, a critical pathogenic element of F. nucleatum, inflicts substantial detriment to human intestinal health. Our research focused on the development of recombinant Lactobacillus plantarum that expresses FomA protein, demonstrating its potential in protecting mice from severe IBD induced by F. nucleatum. To commence, two recombinant strains, L. plantarum NC8-pSIP409-pgsA'-FomA and NC8-pSIP409-FnBPA-pgsA'-FomA, were successfully developed. Validation of the results was achieved through flow cytometry, ELISA, and MTT assays. It was observed that recombinant L. plantarum instigated mouse-specific humoral immunity and elicited mucosal as well as T cell-mediated immune responses. Significantly, it amplified the immune reaction of B cells and CD4 + T cells, facilitated the secretion of cytokines such as IgA, IL4, and IL10, and induced lymphocyte proliferation in response to FomA protein stimulation. Lastly, we discovered that administering recombinant L. plantarum could protect mice from severe IBD triggered by F. nucleatum, subsequently reducing pathological alterations and inflammatory responses. These empirical findings further the study of an innovative oral recombinant Lactobacillus vaccine.